IMMIGRANT ENTREPRENEURSHIP, RELIGION AND ETHNICITY CASES FROM EUROPE, AFRICA (ROUTLEDGE, 2025)
International migration is a growing phenomenon in the 21st century and is increasingly seen as a high-priority public policy issue by many governments, politicians, and the broader public throughout the world. Its importance to economic prosperity, human development, and safety and security ensures that it will remain a top priority for the foreseeable future.This book highlights the importance of ensuring that we remain focused on the successes of migration as well as the challenges. At the end of the 20th century, more importance was given to immigrant and ethnic minority entrepreneurship due to its positive impact on local economic growth and overall economic development in the hosting nations. In the 21st century, the imperative of the United Nations 2030 agenda involves a deeper understanding of the complex challenges for the achievement of sustainable goals. One of these challenges is to understand how migrant-entrepreneurs may or may not identify with their ethnic community, therefore dissociating themselves from their ethnic group. In this sense, religion and ethnicity are differentiating factors between social groups, and the relationships allow preserving their culture and establishing relationships and integration in the community at all levels. This edited volume brings together impactful contributions that will interest multidisciplinary academic areas and aims to contribute to the enhancement of scientific knowledge on the intersection of entrepreneurship, migration, ethnicity, and religion, a gap in the existing literature that has the potential to provide a deeper understanding of factors that influence migrant populations' contribution to socio-economic development in their communities.This book will be an invaluable resource to researchers and scholars in the fields of immigration, immigrant entrepreneurship, entrepreneurial culture, and economic development.
Keywords: Immigrant business enterprises.; Immigrants -- Spiritual life.; Immigrants -- Religious life.; Ethnicity.; elektronické knihy; electronic books